Els auxiliars dels temps compostos en català medieval - Ramos, Joan Rafael (Caplletra. Revista Internacional de Filologia, 2005)
The study of auxiliary verbs in compound tenses («haver» vs. «Ésser») in Old Catalan is a topic discussed in many works. But no research deeply analysing literary works of the time and using an accurate methodology is available. Our purpose is to show that so significant medieval literary works such as «Llibre de Meravelles» by Ramon Llull, «Llibre dels Fets» by King James I & «Tirant lo Blanch», can also provide very valuable information to understand the phenomenon of change of auxiliary. Referring to usage frequencies, we show that chronology plays a great role in these alternations and outline a whole series of factors that explain the observed evolutive tendencies.